Capturing Initial Understanding and Impressions of Surgical Therapy for Parkinson's Disease - Das, Somnath; Matias, Caio M.; Ramesh, Sunidhi; Velagapudi, Lohit; Barbera, Julie P.; Katz, Samantha; Baldassari, Michael P.; Rasool, Mohammad; Kremens, Daniel; Ratliff, Jeffrey; Liang, Tsao-Wei; Wu, Chengyuan (Frontiers in Neurology, 2021)
Background: Deep Brain Stimulation (DBS) is an underutilized surgical therapy for Parkinson’s Disease (PD). Both physician and patient hesitancies have been described as potential barriers to DBS, but the specifics of patient perceptions of DBS have not been well characterized in the general PD population. Objective: To characterize the understanding and impressions of surgical therapy in PD patients prior to formal surgical evaluation. Methods: A 30-question survey assessing impressions of surgical therapy for PD and understanding of DBS for PD was administered to PD patients seen at an urban movement disorders clinic. Results: 102 patients completed the survey. When asked if they would undergo a hypothetical risk-free, curative brain surgery for PD, 98 patients responded “yes.” Patients were more agreeable to “reversible,” “minimally-invasive,” and “incisionless” surgery. 51.2% thought DBS is an “effective” treatment for PD, 76.6% thought it was “invasive,” and 18.3% thought it was “reversible”. 45.2% reported fear of being awake during DBS surgery. Regarding costs, 52.4% were concerned that DBS was “very expensive” or “not covered by insurance.” Initial source of information and perceived treatment effectiveness were not associated with concerns about DBS effectiveness or threats to normality. Negative perceptions of past surgery were associated with concerns about DBS altering mood and personality. Conclusion: Overall, patients expressed concerns regarding procedural efficacy, invasiveness, cost, and irreversibility – independent of the original source of information. Future studies are required to allow us to better understand the impact of these initial findings on DBS hesitancy and underutilization.